The interaction of online co-creative performance in a paired-player mode with creative tendency as a moderator - Wu, Ching-Lin (Frontiers in Psychology, 2025)
This study investigated the moderating effect of individuals’ creative tendencies on their creative performance in interactive situations. A sample of 292 participants was selected to engage in various assessments, including the Alternative Uses Test (AUT) and the Chinese Radical Remote Associates Test (CRRAT) in single-player and paired-player modes. Additionally, participants completed the Creative Tendency Scale (CTS) as part of the data collection process. The collected performance data were used to analyze whether the creative performance of groups with different creative thinking abilities in interactive situations was moderated by creative tendency. The results revealed that risk-taking, curiosity, and total score for creative tendency moderated the relationship between CRRAT performance in single- and paired-player modes. In the context of high risk-taking, curiosity, and total score for creative tendency, the high- and low-scoring CRRAT groups showed no significant differences in their CRRAT performance in the paired-player mode. Moreover, creative tendency did not moderate the relationship between divergent thinking performance in the single- and paired-player modes. Overall, this study distinguishes the impact of creative tendency on the relationship between two types of creative problem-solving (i.e., AUT and CRRAT) in single- and paired-player modes, deepening our understanding of the connection between the cognitive and affective aspects of creativity in different contexts and how individuals exhibit their creativity in one-on-one interactive situations.